(untitled) (SAARC Journal of Agriculture, 2015)
Inheritance of fertility restoration was studied in crosses involving ten elite restorer lines of rice viz. BR827R, BR168R, BR6723-1-1-2R, M.H.63R, M.H.77R, Gui99R, IR40750R, IR64R, AjayaR and IR44675R and one male sterile line II32A with ID (Indonesian paddy type) sources of cytoplasmic male sterility. The segregation pattern for pollen fertility of F2 and BC1 populations of crosses involving II32A indicated the presence of two independent dominant fertility restoring genes. The mode of action of the two genes varied in different crosses revealing three types of interaction, i.e. epistasis with dominant gene action, epistasis with recessive gene action, and epistasis with incomplete dominance. SAARC J. Agri., 13(1): 207-215 (2015)